2020
DOI: 10.1007/s40261-020-00899-2
|View full text |Cite|
|
Sign up to set email alerts
|

Loteprednol Etabonate (Submicron) Ophthalmic Gel 0.38%: A Review in Post-Operative Inflammation and Pain Following Ocular Surgery

Abstract: Loteprednol etabonate ophthalmic gel 0.38% (Lotemax ® SM; hereafter referred to as loteprednol etabonate gel 0.38%) is a topical ophthalmic corticosteroid approved in the USA for the treatment of post-operative inflammation and pain following ocular surgery. This formulation provides improved drug delivery compared with loteprednol etabonate micronized gel 0.5%, with a smaller drug particle size (in the submicron range) to improve dissolution and penetration into ocular tissues, meaning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Both the LE gel 0.5% and LE SM gel 0.38% formulations have similar rheological properties with nearly identical shear-thinning behavior and decreased viscosity on dilution with saline; however, the LE SM gel 0.38% formulation has a reduced drug particle size (an approximately five- to tenfold reduction in diameter), which results in improved drug dissolution, leading to enhanced ocular penetration and bioavailability in the anterior segment tissues most relevant to postsurgery inflammation [ 6 , 7 ]. The reduced particle size in the LE SM gel 0.38% formulation allows for reductions in the active drug concentration and dosing frequency compared with the LE gel 0.5% formulation (three times daily vs. four times daily, respectively) [ 7 ]. Although particle size is reduced in the LE SM gel 0.38% relative to the LE gel 0.5%, both formulations have similar nonsettling properties [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both the LE gel 0.5% and LE SM gel 0.38% formulations have similar rheological properties with nearly identical shear-thinning behavior and decreased viscosity on dilution with saline; however, the LE SM gel 0.38% formulation has a reduced drug particle size (an approximately five- to tenfold reduction in diameter), which results in improved drug dissolution, leading to enhanced ocular penetration and bioavailability in the anterior segment tissues most relevant to postsurgery inflammation [ 6 , 7 ]. The reduced particle size in the LE SM gel 0.38% formulation allows for reductions in the active drug concentration and dosing frequency compared with the LE gel 0.5% formulation (three times daily vs. four times daily, respectively) [ 7 ]. Although particle size is reduced in the LE SM gel 0.38% relative to the LE gel 0.5%, both formulations have similar nonsettling properties [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reduced particle size in the LE SM gel 0.38% formulation allows for reductions in the active drug concentration and dosing frequency compared with the LE gel 0.5% formulation (three times daily vs. four times daily, respectively) [ 7 ]. Although particle size is reduced in the LE SM gel 0.38% relative to the LE gel 0.5%, both formulations have similar nonsettling properties [ 7 ]. Furthermore, modifications made to the excipients in the LE SM gel 0.38% formulation to stabilize the drug particles (e.g., hypromellose) [ 1 , 6 ] do not appear to affect the nonsettling characteristics of this formulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature does not clearly establish an optimal AIM regimen, dosing, or duration of treatment. [1][2][3][4][5][6][7][8] Some ophthalmologists prescribe either corticosteroids or NSAIDs as topical monotherapy; others prescribe both in combination, potentially as a result of the ESCRS randomized clinical trial that showed that patients treated with combination therapy had a reduced likelihood of developing clinically significant cystoid macular edema compared with those receiving topical monotherapy. 9 More recently, alternate routes of corticosteroid administration have been tried and adopted in an effort to reduce the need or frequency of topical AIM.…”
mentioning
confidence: 99%